Water usage reduction and CSR committees: Taiwan evidence - Chen, Yu‐Lin; Huang, Mei‐Chu (Corporate social-responsibility and environmental management, 2023)
Although board‐level corporate social responsibility (CSR) committees have been discussed extensively, we know relatively little about how CSR committees affect companies' water conservation and the contingencies that influence this relationship, specifically in emerging markets. In Taiwan, industrial water conservation is an imperative climate change adaptation given the elevating incidence of floods and droughts brought on by climate change. This study extensively hand‐collects data on water usage, the existence of CSR committees from CSR reports, and the annual reports of companies listed on the Taiwan Stock Exchange and Taipei Exchange companies during 2017–2020. Our findings support the stakeholder theory that the existence of CSR committees likely set water use reduction targets and facilitated water usage reduction. Moreover, this relationship is stronger in water consumption industries. In summary, the memberships in water consumption industries and CSR committees are complements rather than substitutes.